2001
DOI: 10.1002/1521-4141(200112)31:12<3432::aid-immu3432>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of cross presentation of vaccinia virus-derived antigens by human dendritic cells

Abstract: Dendritic cells (DC) utilize at least two pathways to process viral antigens onto MHC class I molecules. The conventional endogenous route is used to acquire antigens from both infectious and non‐replicating virions. Exogenous pathways are used by DC to acquire and "cross‐present" antigens derived from virus‐infected donor cells that by themselves lack the ability to activate T cells directly. We analyzed the role of this pathway for antigens derived from vaccinia, a virus which inhibits DC maturation and caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 36 publications
3
51
1
Order By: Relevance
“…It is also likely that part of the Ag presentation occurring in vivo could be dependent upon endogenous scavenger DC that, upon virally induced cell death at the vaccination site or in draining lymph nodes, can cross-present rVV-derived Ag. 4,55,56 Although rVV infection has been shown to impede maturation of DC, 24 it does not appear, according to our study, to rapidly revert the function and properties of DC after completion of the maturation process. In fact, rVV infection only minimally affected the status of maturation of DC in the experimental conditions tested here.…”
Section: Epitope Selection In Vaccinia-virus-infected Dendritic Cellscontrasting
confidence: 53%
“…It is also likely that part of the Ag presentation occurring in vivo could be dependent upon endogenous scavenger DC that, upon virally induced cell death at the vaccination site or in draining lymph nodes, can cross-present rVV-derived Ag. 4,55,56 Although rVV infection has been shown to impede maturation of DC, 24 it does not appear, according to our study, to rapidly revert the function and properties of DC after completion of the maturation process. In fact, rVV infection only minimally affected the status of maturation of DC in the experimental conditions tested here.…”
Section: Epitope Selection In Vaccinia-virus-infected Dendritic Cellscontrasting
confidence: 53%
“…DC are believed to initiate antiviral CD8 + T cell responses either after direct infection or by cross-priming with antigens from other infected cells. In the case of vaccinia, DC have been shown to be able to efficiently cross-present viral antigens from other infected cells both in vitro [23] and in vivo following subcutaneous inoculation [24]. In this article, we show that an A39R-induced decrease in particle uptake by DC in vivo may result in inhibition of their ability to crossprime CD8 + T cells ex vivo.…”
Section: Discussionmentioning
confidence: 78%
“…First, VV induces extensive cell death through both apoptotic and necrotic pathways, providing an abundance of cellular material for ingestion by DCs. 24,33 Second, the expression of CD40L on tumor cells infected with rV-CD40L further enhances TAA presentation by DCs, Despite this scenario, we found that the interaction of immune cells with rV-CD40L-infected tumor cells creates a complicated network of interactions with a high degree of unpredictability.…”
Section: Dx5 þ (Nk/nkt) Cells Proliferate and Release Ifn-g In Responmentioning
confidence: 82%
“…While DC infected with recombinant VV can induce CD8 þ T-cell responses against the virus and foreign antigens, other studies suggest that VV immunogenicity is mediated by crosspresentation of vacciniaderived antigens from apoptotic or necrotic VV-infected cells. 23,24 Viral immunogenicity may also be influenced by cellular antigens that are carried by VV particles acquired from host cells in culture. 25,26 This occurs due to the life cycle of VV within the cytoplasm of infected cells, where intracellular membranes are incorporated into intracellular enveloped virus (IEV) or cell membrane components are captured by the virus during assembly of extracellular enveloped virus (EEV) particles.…”
mentioning
confidence: 99%